"Listening Silence" and Its Discursive Effects. Issue 3 (June 2016) - Applebaum, Barbara
ABSTRACT: While researchers have studied how white silence protects white innocence and white ignorance, in this essay Barbara Applebaum explores a form of white silence that she refers to as "listening silence" in which silence protects white innocence but does not necessarily promote resistance to learning. White listening silence can appear to be a constructive pedagogical tool for teaching white students about their implication in the perpetuation of racism. The truth of white students' listening may make it seem as if silence promotes what George Yancy refers to as "tarrying" with a critique of whiteness. Applebaum argues, however, that white listening silence is itself a manifestation of complicity and needs to be disrupted. This examination expands discussions of white silence in the scholarship not by providing a formula for when silence is or is not pedagogically necessary, but rather by demonstrating that listening silence is not a form of "tarrying." The first section examines the unique features of listening silence and the relationship between silence, ignorance, and innocence. The second section critically examines white listening silence in cross‐cultural dialogues and draws upon the work of Linda Martin Alcoff to argue that listening silence must be understood within the discursive context in which it is practiced. Finally, three implications of this emphasis on the discursive context for the role of silence in tarrying with the critique of whiteness are discussed.